Identification of Major Saponins from Jiaogulan Extract (Gynostemma pentaphyllum) - Niramon Utama-ang; Penkwan Chompreeda; Vichai Haruthaithanasan; Nusiri Lerdvuthisopon; Thongchai Suwonsichon; Karl Wood; Bruce A. Watkins (Agriculture and Natural Resources, 2006)
Jiaogulan (Gynostemma pentaphyllum; GP) contained a saponin glycoside which was related to ginseng saponin. The purpose of this study was to identify the main saponin in water extract GP compared to methanol and ethanol extract. The sample was prepared by alkaline cleavage, trimethylsilyl (TMS) derivatization and gas chromatographic-mass spectrometric (GC-MS) analysis comparison with standard ginsenoside Rb1. The results showed that there were two main dammarant type aglycones in water, methanol and ethanol extracts GP, 20(S)-dammar-24-ene-3β, 12β, 20 triol and 20(S)-dammar-24-ene-3β, 6α, 12β, 20 tetrol, which were the same compound as ginsenoside Rb1 and Rg1 from ginseng (Panax spp.), representatively. The other peak, 20(S)-dammar-24-ene-3β, 12β, 19, 20 tetrol, was not obvious in water extract as in methanol and ethanol extracts. In conclusion, the water extract GP contained two main saponin compounds, which were the same compounds as in ginseng.